Regional differences in income distribution in Colombia - Bonilla Mejía, Leonardo (Sociedad y Economía, 2011)
This paper characterizes the regional differences in income distribution in Colombia, focusing on three big questions: First, ¿how important are these regional differences, and more specifically, how much do they account for in total income inequality? Second, ¿does income inequality gaps have a regional pattern? And finally, is there any relationship between inequality and income level? Evidence indicates that the regional differences in income distribution in Colombia are significant. We also found that the most egalitarian departments and cities are those of middle income, while the richest are usually among the least equal